2022
DOI: 10.3389/fcimb.2022.909799
|View full text |Cite
|
Sign up to set email alerts
|

Gardnerella Exposures Alter Bladder Gene Expression and Augment Uropathogenic Escherichia coli Urinary Tract Infection in Mice

Abstract: The anaerobic actinobacterium Gardnerella was first isolated from the bladder by suprapubic aspiration more than 50 years ago. Since then, Gardnerella has been increasingly recognized as a common and often abundant member of the female urinary microbiome (urobiome). Some studies even suggest that the presence of Gardnerella is associated with urological disorders in women. We recently reported that inoculation of Gardnerella into the bladders of mice results in urothelial exfoliation. Here, we performed whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The quantitative nature of the microbial whole genome sequencing (WGS) method identifies traditional uropathogens in low numbers in samples characterized by infection. Gilbert et al [ 29 ] used mouse bladder RNA-Seq data to point out the shedding and differentiation of uroepithelial cells affected by Gardnerella exposure, promoting the persistence of uropathogenic E. coli (UPEC) in the bladder. Nonetheless, research is ongoing to fully understand the precise mechanisms driving the development and maintenance of the urinary microbiota.…”
Section: Human Microbiota and Utimentioning
confidence: 99%
“…The quantitative nature of the microbial whole genome sequencing (WGS) method identifies traditional uropathogens in low numbers in samples characterized by infection. Gilbert et al [ 29 ] used mouse bladder RNA-Seq data to point out the shedding and differentiation of uroepithelial cells affected by Gardnerella exposure, promoting the persistence of uropathogenic E. coli (UPEC) in the bladder. Nonetheless, research is ongoing to fully understand the precise mechanisms driving the development and maintenance of the urinary microbiota.…”
Section: Human Microbiota and Utimentioning
confidence: 99%
“…Similar to this gut-bladder axis, vaginal dysbiosis may prompt a UTI via the vagina-bladder axis as a reservoir for uropathogens such as E. coli ( 6 ). Although G. vaginalis is a rare cause of symptomatic UTI, an in vitro study showed that G. vaginalis altered bladder gene expression and increased susceptibility to subsequent UTI caused by uropathogenic E. coli ( 141 ). Compared to women without BV, those with BV have a significantly increased risk of UTI, with an odds ratio of 13.75 ( 142 ), and a clinical trial showed that the efficacy of intravaginally administered L. crispatus probiotics reduced the recurrence of UTI ( 143 ).…”
Section: Vagina-bladder Axismentioning
confidence: 99%
“…Compared to women without BV, those with BV have a significantly increased risk of UTI, with an odds ratio of 13.75 ( 142 ), and a clinical trial showed that the efficacy of intravaginally administered L. crispatus probiotics reduced the recurrence of UTI ( 143 ). Furthermore, as G. vaginalis is often detected in the urinary microbiota ( 141 ), the urine microbiota may prompt BV via the vagina-bladder axis as a reservoir for G. vaginalis .…”
Section: Vagina-bladder Axismentioning
confidence: 99%